Modified self-obtained pooled sampling to screen for Chlamydia trachomatis and Neisseria gonorrhoeae infections in men who have sex with men. Issue 5 (20th October 2020) - Ando, Naokatsu; Mizushima, Daisuke; Watanabe, Koji; Takano, Misao; Shiojiri, Daisuke; Uemura, Haruka; AOKI, Takahiro; Yanagawa, Yasuaki; Kikuchi, Yoshimi; Oka, Shinichi; Gatanaga, Hiroyuki
Abstract : Objectives: To assess whether pooled sample testing with nucleic acid amplification tests was a potential alternative to three single-site sample testing to screen for Chlamydia trachomatis and Neisseria gonorrhoeae infections in asymptomatic men who have sex with men. Methods: We prospectively compared pooled sample testing with single-site sample testing in asymptomatic MSM. Self-obtained paired rectal samples, one gargle sample and one first-void urine sample were collected from participants to generate two sets of samples: one for pooled sample testing and the other for single-site testing. We used modified pooled sampling, which is defined as the use of gargle samples, instead of swabs, for the pooled sample to test for pharyngeal infection. Results: This study included 513 MSM. The positive rates of C. trachomatis and N. gonorrhoeae were 20.3% and 11.7%, respectively, for single-site sample testing. Compared with the sensitivity of single-site testing as the gold standard, the sensitivities of pooled sample testing for C. trachomatis and N. gonorrhoeae were 94.2% (95% CI 88.0% to 97.3%) and 98.3% (95% CI 90.9% to 99.9%), respectively. The concordance rate and kappa coefficient were 98.3% (95% CI 96.7% to 99.2%) and 0.945 (95% CI 0.859 to 1.000), respectively, for C. trachomatis and 98.8% (95% CI 90.1% to 100%) and 0.943 (95% CI 0.857 to 1.000), respectively, for N. gonorrhoeae . Conclusions: The modified pooled sampling had a comparably high consistency with single-site sample testing. The results strongly suggest that the gargle sample is suitable as a part of pooled sample for STI screening of C. trachomatis and N. gonorrhoeae .